Gambaran Tingkat Pengetahuan Remaja Masjid At-Taqwim Terhadap Kesehatan Reproduksi Remaja - Talitha Syafira Nurhayati; Putra Apriadi Siregar (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Adolescence is the period when the development of the reproductive organs begins. Adolescents' lack of knowledge about reproductive health can cause problems in their reproductive health. Many problems will arise as a result of neglecting reproductive health, namely unwanted pregnancy, abortion, marriage and early marriage, STIs or STDs and HIV/AIDS. The purpose of this study was to describe the level of knowledge of adolescents about reproductive health. This study used a descriptive design with a survey approach, the method of taking samples used total sampling, with a total sample of 32 people. Data collection using google form. The results of the study showed that 18 respondents (56.3%) had good knowledge.